ANTESEDEN PENERAPAN MANAJEMEN RISIKO DAN PENGARUHNYA TERHADAP NILAI PERUSAHAAN - Muhammad Agus; Atma Hayat (Universitas Lambung Mangkurat, 2021)
The objective of this research is to analyze the effect of firm ownership, firm size, diversification, and good corporate governance on risk management implementation, and effect of risk management on firm value in the basic industry and chemicals sector listed on the IDX from 2016 to 2019.The research employs an explanatory method with a unit of analysis that focuses on the annual financial statements of companies in the basic industry and chemicals sector, with a population totaling 72 companies, and a sample of 40 companies using the purposive sampling technique. In addition, tests were conducted while the validity and reliability tests using smartpls software.According to the findings of this research, firm size, diversification, and good corporate governance have a significant effect on risk management implementation, while firm ownership does not have a significant effect on risk management implementation. Furthermore, risk management does not have a significant effect on the firm value.